Fungsi Penguasaan Ragam Bahasa Gaul pada Remaja Tunarungu Genetis di SLB Negeri Semarang - Rizda Mayerlandy; Muhammad Suryadi; Mujid Farihul Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
Slang is a variety of Indonesian made by teenagers which later becomes the language often used by teenagers to establish daily communication with their friends. Although not taught through formal education, slang is also acquired, used, and understood by deaf youth groups with limited language acquisition processes. The purpose of this study was to identify language functions that arise when deaf adolescents use various slang to communicate. This research is a qualitative research using in-depth interviews on a subject that has been determined using the purposive sampling method. Data analysis was carried out in three stages, namely reduction, display, and data verification. Then the collected data were analyzed using Bloom's behavioral theory and language function theory. The results of this study are the functions of using slang which are widely used by deaf teenagers in SLB Negeri Semarang, namely emotive, conative, and tired functions.